ADSORPTIVE REMOVAL OF ORGANIC CHEMICALS FROM AQUEOUS SOLUTION BY SOIL EQUILIBRIUM STUDY - Tembhre Nandini, Singh B. K., Soni Monika (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
The potential of soil, a low cost and abundantly available material with good sorption properties, for removing aromatic organic compound was investigated. Nitro-benzene, Clorobenzene, Bromobenzene, Benzene, Phenol, O-cloro phenols, M-Cloro phenol, P-Cloro phenol, Benzaldehyde , Aniline, O-Chloro Aniline ,M- Chloro aniline, P-Chloro aniline, Toluene , were selected for the studies. The effect of various factors such as adsorbent particle size, pH, phenol concentration and temperature on the sorption capacity was investigated. Langmuir adsorption isotherm constants were calculated and it was shown that the adsorption data for aromatic organic compound onto soil fitted the Langmuir model well. It was found that these low cost soil adsorbent demonstrated good removal capability of Nitro-benzene, Clorobenzene, Bromobenzene, Benzene, Phenol, O-cloro phenols, M-Cloro phenol, P-Cloro phenol, Benzaldehyde , Aniline, O-Chloro Aniline ,M-Chloro aniline, P-Chloro aniline, Toluene , hence can be used economically on large scale.